Association between the Level of Emotional Intelligence and Nurses' Caring Behavior Based on Patients'/Families' Perceptions at RSUD Toto Kabila, Bone Bolango Regency. - Clara Alvioni Puteri I Mohamad; Nasrun Pakaya; Dewi Suryaningsi Hiola (Cita konsultindo, 2026)
Caring behavior is the core of nursing services that enhance human dignity and support recovery, particularly among critically ill patients in intensive care units that depend heavily on nurses. Emotional intelligence is one internal factor influencing caring behavior, referring to the nurses' ability to recognize and manage their own emotions, motivate themselves, understand others' emotions, and build social relationships. This research aims to analyze the association between emotional intelligence and nurses' caring behavior, as perceived by patients and families, in the ICU/ICCU of RSUD (Regional General Hospital) Toto Kabila, Bone Bolango Regency. This research employs a quantitative approach with a cross-sectional design, involving 38 respondents selected through consecutive sampling, and uses instruments that have been tested for validity and reliability, including questionnaires on emotional intelligence and nurses' caring behavior. The results indicate that most nurses demonstrate a high level of emotional intelligence (37 respondents, 97.4%) and that nurses' caring behavior is predominantly rated as good (35 respondents, 92.1%). Based on the Spearman Rank test, a p-value of 0.029 (<0.05) is obtained, indicating a positive association between emotional intelligence and nurses' caring behayon with a moderate level of correlation. In conclusion, a higher level of emotional Intelligence is associated with better caring behavior